Effects of slag addition on bond strength of 3D printed geopolymer mortar : an experimental investigation - Noor Mohamed, Nisar Ahamed (2018)
3D concrete printing is gaining ground in the construction industry. In concrete printing, fresh concrete layers are deposited layer by layer manner like fused deposition modelling process following a computer-aided design (CAD) model. The structural capacity of the printed part mainly depends on the bond strength between the old substrate and new overlaid concrete. Hence, it is essential to measure the inter layer bond strength and its influencing parameters. In this paper, a novel geopolymer ink is considered as reference material, that exhibits thixotropic property, suitable for 3D printing application. The said geopolymer thixotropic build up rate was altered by adding slag in two different percentages. From the experimental outcomes, it was found that, rapid structural build-up and long delay time can cause poor bonding in the interface properties of the printed structure. This delay time depends strongly on the thixotropic behavior, the thickness of the layers and roughness of the interface between the two layers.